PENGARUH UKURAN KAP, PERGANTIAN MANAJEMEN, OPINI GOING CONCERN TERHADAP AUDITOR SWITCHING PADA PERUSAHAAN REAL ESTATE DAN PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019 -2021 - Devi Auliya Styaningsih; Antoni (Jurnal Ekonomi dan Bisnis, 2023)
Auditor switching is the process of changing auditors or accounting firms carried out by a company. Auditor switching can be implemented either mandatory or voluntary. Auditor switching voluntarily which usually creates a sense of suspicion among stakeholders. The purpose of this study is to examine and analyze the effect of KAP size, management turnover, going concern opinion on auditor switching. The population in this study are Real Estate and Property companies listed on the IDX for the period 2019 - 2021. Using a purposive sampling technique with the results of 35 companies. The data used is in the form of secondary data through documentary data collection techniques. Data analysis techniques used descriptive statistics and logistic regression analysis with a sig.<0.05 level. The results of this study indicate that KAP size partially has a significant effect on Auditor Switching, Management Change and Going Concern Opinion partially has no significant effect on Auditor Switching and KAP Size, Management Change, Going Concern Opinion simultaneously has a significant effect on Auditor Switching.